If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 * 4p + -5 * 3r + 3 * 3q + -5 * 5r + 4 * 5q + -10q = 0 Multiply 7 * 4 28p + -5 * 3r + 3 * 3q + -5 * 5r + 4 * 5q + -10q = 0 Multiply -5 * 3 28p + -15r + 3 * 3q + -5 * 5r + 4 * 5q + -10q = 0 Multiply 3 * 3 28p + -15r + 9q + -5 * 5r + 4 * 5q + -10q = 0 Multiply -5 * 5 28p + -15r + 9q + -25r + 4 * 5q + -10q = 0 Multiply 4 * 5 28p + -15r + 9q + -25r + 20q + -10q = 0 Reorder the terms: 28p + 9q + 20q + -10q + -15r + -25r = 0 Combine like terms: 9q + 20q = 29q 28p + 29q + -10q + -15r + -25r = 0 Combine like terms: 29q + -10q = 19q 28p + 19q + -15r + -25r = 0 Combine like terms: -15r + -25r = -40r 28p + 19q + -40r = 0 Solving 28p + 19q + -40r = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-19q' to each side of the equation. 28p + 19q + -19q + -40r = 0 + -19q Combine like terms: 19q + -19q = 0 28p + 0 + -40r = 0 + -19q 28p + -40r = 0 + -19q Remove the zero: 28p + -40r = -19q Add '40r' to each side of the equation. 28p + -40r + 40r = -19q + 40r Combine like terms: -40r + 40r = 0 28p + 0 = -19q + 40r 28p = -19q + 40r Divide each side by '28'. p = -0.6785714286q + 1.428571429r Simplifying p = -0.6785714286q + 1.428571429r
| 3x/4-12=3 | | 2w+1+w=18 | | 0.36(24)+0.04=0.12(6+x) | | 11*11/12-3 | | 8x+4=-2(6x-1) | | y-5=2/4(x-2) | | 7x+5(2+x)=-2 | | (1/3)8 | | 3-4x=2x+25 | | 6x+3=34x+7 | | 23-[3+9y-3(y+3)]=-3(4y-6)-[8(y-1)-10y+13] | | 3(2x+6)+12=-15 | | 5(1-3m)=30-(4m+7) | | 3x-4.9=0 | | x^2-3ax-10a^2=0 | | 7y+6=2y-9 | | 12(3x+4)-5(2x-5)=6x-67 | | 13r+16=5t | | -5-10b=15-11b | | (0.2x+3)(0.2x-3)=0 | | 4[x+2(5-x)]=3x+1 | | 15+11h=10h | | 12y-6+2y+8=12solve | | 5x-3x=7 | | -15+3j=13+5j | | x^2-0.4x+0.0425=0 | | 3+6x=x+16 | | A(x)=4x^2+20x | | 1/x-1/7=7 | | 12=-3(4x-8) | | 6y-10-3y+5=0 | | 92=5k+4(-4k+1) |